Resistance of oats to smut diseases in the forest-steppes of the Pre-Ob region - N. P. Bekhtold; E. A. Orlova (Зерновое хозяйство России, 2022)
Loose smut (Ustilago avenae (Pers.) Jens.) and covered smut (Ustilago kolleri Wille) are considered to be the most harmful and widespread in the forest-steppes of the Pre-Ob region. The poor grain yields in some years could reach up to 25%, and up to 50% in the years of epiphytoties. The purpose of the current study was to identify the resistance of oat varieties to dusty and covered smut in the forest-steppes of the Pre-Ob region. The study was carried out at the phytopathological plot of the laboratory for plant gene pool of the SRIPCB, the branch of Institute of Cytology and Genetics, Siberian Branch of RAS in 2018–2021. The objects of research were Russian varieties from the world collection of VIR named after V.I. Vavilov. There have been studied 64 oat genotypes for resistance to local populations of loose and covered smut. There has been established a significant correlation between plants’ damage caused by loose and covered smut and soil temperature during the period ‘third decade of May – the first decade of June’ (r = 0.76 and r = 0.73). There was no significant correlation between plants’ damage and the average daily air temperature (r = 0.32 and r = 0.48). There has been determined a negative relationship (r = –0.77 and r = –0.71) between the manifestation of the disease and the amount of precipitation during the period ‘sowing-sprouts’. There has been established that most varieties are susceptible to pathogens. According to smut fungi resistance under conditions of an artificial infectious background, there have been identified such oat varieties as ‘Sibirsky Gerkules’, ‘Fakel’, ‘Rysak’ and ‘Uralets’. These varieties are characterized by large productivity, 1000-grain weight, resistance to lodging.